Learning Disability of Fifth Grade Students with Learning Difficulties at Karak Governorate and its Relationship to Academic Self-Efficacy - Al-Shobaki, Tahani (Dirasat: Educational Sciences, 2022)
Objectives: This study aims to identify the level of learning disability of fifth grade female students with learning difficulties at Karak Governorate, Jordan, and its relationship to the level of academic self-efficacy. Methods: The study followed a relational descriptive approach. The study sample consisted of (150) students from Karak Governorate, Jordan. The researcher used two measures of learning disability that have (22) paragraphs, and a measure of academic self-efficacy that has a number of (20) paragraphs. The validity and reliability of the two scales were verified. Results: The results of the study showed that the level of learned disability and academic self-efficacy among fifth-grade students with learning difficulties, from their viewpoint, was high. The results also showed a lack of a positive correlation between the level of learner disability and the level of academic self-efficacy. Conclusions: The study recommends increasing Interest in conducting training programs to improve academic self-efficacy among female students by focusing on providing female students with necessary skills.